Selection of Suitable Sites for Rainwater Harvesting Structures in the Northern of Iraq: A Review - Obeid, Zahraa H.; Abbas, Abdulhussain A.; Hamza, Zuhal Abdulhadi (Basrah Journal for Engineering Sciences, 2025)
Since the 1970s, rainwater harvesting has gained more attention, specifically in semi-arid and arid areas. It is essential to take into account how much water can be collected from a single catchment site. Rainfall that has been harvested provides an alternative source of water in the northern region of Iraq. Numerous scholars have developed and executed a range of strategies and guidelines to choose appropriate locations and methods for rainwater harvesting (RWH). However, choosing the optimal method or set of rules for the choice of site is challenging. This study’s primary goal was to evaluate previous research regarding the selection of appropriate RWH locations in northern Iraq by assembling a list of the most important techniques and guidelines that evolved over the previous thirty years. The primary factors considered in the process of choosing acceptable locations for RWH were soil type, slope, land use/cover, rainfall, and runoff. A literature review for RWH indicated that these criteria were chosen more frequently and significantly, and the opinions of experts should be used to establish the weight of each criterion. The majority of studies select RHW sites using geographic information systems, hydrological models, and multi-criteria analysis.